The politics of energy security critical security studies, new materialism and governmentality - Kester, Johannes (Routledge explorations in energy studies, 2018)
The Politics of Energy Security unpacks three social practices that drive energy security. These include an analysis of the logics of security, a study of the relation between the materiality of sociotechnical (energy) systems and the knowledge people have over such systems, and a reflection on the power and politics behind (energy) security. This book will be of great interest to students and scholars of energy security and policy, political theory, international relations, critical security studies and environmental studies more broadly.